Technology enhanced peer learning and peer assessment - Henriksen, Christian Bugge; Bregnhøj, Henrik; Rosthøj, Susanne; Ceballos, Alejandro; Kaas, Henrik; Harker-Schuch, Inez; Andersen, Ingelise; Larsen, Søren; May, Michael (Tidsskriftet Læring og Medier (LOM), 2016)
This paper explores the application of learning designs featuring formalised and structured technology enhanced peer learning. These include student produced learning elements, peer review discussions and peer assessment in the BSc/MSc level summer course Restoration of European Ecosystems and Freshwaters (REEF), the Master thesis preparation seminars for the Master of Public Health (MPH) and the MOOC course Global Environmental Management (GEM). The application of student produced learning elements and peer review discussions is investigated by analyzing quotes from course evaluations and performing focus group interviews. The application of peer assessment is investigated by analyzing the agreement of peer assessment between students assessing the same assignment. Our analyses confirm previous research on the value of peer learning and peer assessment and we argue that there could also be a huge benefit from developing learning design patterns that facilitate informal peer learning and reinforce knowledge sharing practices.